On the theory of PT-symmetric operatorss - Kuzhel', S. A.; Patsyuk, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
This article develops a general theory of PT-symmetric operators. Special attention is given to PT-symmetric quasi-self-adjoint extensions of symmetric operator with deficiency indices 〈 2, 2 〉. For these extensions, the possibility of their interpretation as self-adjoint operators in Krein spaces is investigated, and a description of nonreal eigenvalues is given. These abstract results are applied to the Schrodinger operator with Coulomb potential on the real axis.